Hubungan Mutu Gizi Pangan dan Skor Pola Pangan Harapan (Pph) dengan Status Gizi Balita - Urbanus Sihotang (POLTEKKES KEMENKES MEDAN, 2021)
This study aims to determine the relationship between food nutritional quality and the expected food pattern score (PPH) with the nutritional status of children under five in Palu Sibaji Village, Pantai Labu District. This research was conducted in Palu Sibaji village in June 2018. The design of this study used an observational research design with a cross sectional approach. The results showed that the value of p on the nutritional quality of food variable with = 1,000, while on the variable of food pattern expectations with the nutritional status of children under five = 0.311. In conclusion, there is no relationship between the nutritional quality of food and the expected food pattern score (pph) with the nutritional status of children under five in Palu Sibaji Village, Pantai Labu District. Keywords: Food Nutrition Quality, Expected Food Pattern Score (PPH), Nutritional Status of Toddlers